1999
DOI: 10.5014/ajot.53.5.454
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Occupational Therapists Regarding Postprofessional Education

Abstract: Results suggested that a relatively low number of occupational therapists consider pursuing postprofessional education. Thus, if graduate education is essential for the advancement of the profession, emphasis must be on clarifying the need for and value of postprofessional education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 2 publications
3
13
1
6
Order By: Relevance
“…These findings concur with those of Dickerson and Wittman (1999). Participants were positive about the required residency period in terms of access to resources, libraries and blocks of dedicated time with their supervisor.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…These findings concur with those of Dickerson and Wittman (1999). Participants were positive about the required residency period in terms of access to resources, libraries and blocks of dedicated time with their supervisor.…”
Section: Resultssupporting
confidence: 85%
“…Graduate education provides opportunities for: engaging in personal and professional development; increasing skills and knowledge; career advancement; becoming university faculty; and engaging in clinical research (Dickerson and Wittman, 1999). Pursuing graduate education is essential to developing a scientific approach to practice since it can provide answers to clinical questions as well as contributing theoretical knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cooperative learning framework is advocated as the most effective structure for online learning (Lally & Barrett, 1999). Dickerson and Wittman (1999) found that occupational therapists interested in graduate education wanted coursework that would improve their clinical skills and knowledge. Only one study in the occupational therapy literature has addressed online pedagogy (Simons et al, 2000), and no studies have investigated whether online education can meet the post-professional learning needs of occupational therapists.…”
mentioning
confidence: 99%